Remote light source for silicon photonic transceivers in mobile fronthaul applications. Issue 4 (1st February 2015) - Giorgi, L.; D'Errico, A.; Presi, M.; Ciaramella, E.; Testa, F.
Abstract : The design and experimental characterisation of a depolarised light source for feeding a remote transceiver based on silicon photonics are presented. Since the transceiver only works in TE mode, the source is designed to deliver, over up to 10 km standard single‐mode fibre links, a continuous‐wave light with almost constant power along this polarisation direction, whatever be the random polarisation rotation because of the fibre link. The depolarised light source is realised by combining the output of two independent distributed feedback lasers, having orthogonal polarisation and controlled frequency difference. The transmission performance and stability of the remote light source are successfully tested.